Denmark : Technical Assistance Report-Revenue Administration Gap Analysis Program-The Value-Added Tax Gap. (IMF Staff Country Reports; Country Report ;, 2016)
This report presents estimates of the tax gap for Denmark for the period 2008-12. There are two main components to the RA-GAP methodology for estimating the VAT gap: 1) estimate the potential VAT collections for a given period; and 2) determine the accrued VAT collections for that period. The difference between the two values is the VAT gap. The methodology employs a top-down approach for estimating the potential VAT base, using statistical data on value-added generated in each sector and constructs the accrued VAT collections value from tax record data. One of the main purposes of this report is to estimate the compliance gap. The compliance gap is the difference between the potential VAT that could have been collected given the current policy framework and actual accrued VAT collections. Other tax gap measures can be determined using different methods for determining potential VAT, and these other measures are important in understanding all the factors which are affecting current collections. This report will provide estimates for these other gap measures as well, and compare and contrast them with the compliance gap.